Deciphering magnetic hyperthermia properties of compositionally and morphologically modulated FeNi nanoparticles using first-order reversal curve analysis. (2nd November 2018) - Salati, Alireza; Ramazani, Abdolali; Almasi Kashi, Mohammad
Abstract: Magnetic hyperthermia based on nanoparticles (NPs) is considered a significant approach in cancer therapy. However, less attention has been paid to the correlation between hyperthermia properties and detailed magnetic characteristics. Herein, the hyperthermia capability of Fex Ni100-x (8 ≤ × ≤ 40) NPs synthesized using a polyol method was studied by investigating the temperature rise and specific loss power (SLP) of their ferrofluid (FF) solutions while also performing first-order reversal curve (FORC) analysis. The colloidal stability of magnetic NPs in the FFs was enhanced by coating their surface with polyethylene glycol, and the hyperthermia experiments were carried out in ethylene glycol and DI water (DIW) dispersion media using different concentrations (1.25, 2.5 and 5 mg ml −1 ). A field-emission scanning electron microscope was employed to characterize the morphology of the FeNi NPs, evidencing mean diameters ranging between 64–112 nm. Hysteresis loop measurements showed a decreasing trend of average coercive field from 94 to 52 Oe when decreasing the diameter, coinciding with a 13% increase in the reversible fraction of single-domain and superparamagnetic (SP) NPs, according to FORC results. In this way, the corresponding SLP value increased from 55 to 264 W g −1 for FFs in 1.25 mg ml −1 concentrated DIW medium with an SP fraction of 40%.